Detection and Determination of Staphylococcus aureus in Camel Milk and Associated Factors in Fedis, Eastern Hararghe, Ethiopia. (May 2022) - Tasse, Ibsa; Mengistu, Dechasa Adare; Belina, Dinaol; Girma, Sisay
Background: Camel milk is the key food for pastoralists in the arid and semi-arid areas of the eastern lowlands of Ethiopia. Unless it is handled under good hygienic conditions, milk can be a good medium for bacterial growth and can lead to foodborne diseases caused by various pathogenic microorganisms, such as Staphylococcus aureus . The current study was aimed to determine the prevalence of Staphylococcus aureus in raw camel milk and associated factors in Fedis, Eastern Ethiopia. Methods: A cross-sectional study was conducted from December 2, 2018 to May 26, 2019 in Fedis, Eastern Hararghe, Ethiopia. The questionnaire was used to determine the hygienic practices of camel milkers and sellers. Laboratory analysis was conducted to determine the level of Staphylococcus aureus . A total of 156 (78 from households and 78 from selling sites) milk samples were collected randomly from selected camel herd owners and selling sites for the isolation and enumeration of Staphylococcus aureus . Data analysis was carried out using SPSS software version 22.0. Finally, Chi-square and Fisher's exact tests were used to analyze the data. A P -value of .05 was considered as the cut-off point for statistical significance. Results: A total of 156 samples, including 78 samples of raw milk from the households and 78 samples from the market were purchased to determine Staphylococcus aureus . Out of 156 samples, Staphylococcus aureus was detected in 60 (38.5%) samples, of which 27 (34.6%) and 33 (42.3%) were among those collected from household and market, respectively. The overall mean Staphylococcus aureus count was 4.83 log CFU/mL, with household and market samples accounted for 2.76 and 5.08 log CFU/mL, respectively. Furthermore, 23 (38.3%) of the samples were contaminated with Staphylococcus aureus beyond the recommended level (4-5 log CFU/mL). There was a statistically significant association ( P -value of <.05) between the prevalence of Staphylococcus aureus and other variables such as age of the camel, parity, lactation stages, and sources of milk. Conclusion: More than one-third of milk samples were contaminated with Staphylococcus aureus at levels higher than the maximum permitted level. The findings of the current study suggests that there is a potential risk of foodborne infection and intoxication. Therefore, implementation of adequate hygiene and safety practices is very important to prevent the consumption of contaminated fruit juices, which leads to foodborne illness.